Atrial pacing during radiofrequency deliveries for catheter ablation of para-Hisian arrhythmias. Issue 5 (November 2015) - Miyazaki, Shinsuke; Taniguchi, Hiroshi; Komatsu, Yuki; Nakamura, Hiroaki; Hachiya, Hitoshi; Iesaka, Yoshito
Abstract Background Atrial pacing during radiofrequency (RF) deliveries is a technique to facilitate rapid recognition of impaired atrioventricular (AV) conduction during slow pathway ablation of AV nodal reentrant tachycardia. The objective of our study was to report this technique in the catheter ablation of para-Hisian arrhythmias. Methods The study included a total of 48 patients who underwent ablation of para-Hisian arrhythmias including accessory pathways (APs), atrial tachycardias (ATs), and ventricular arrhythmias (VAs) in 6, 9, and 33 patients, respectively. Results AT was successfully eliminated in all cases without any accelerated junctional rhythm (JR) occurring. JR appeared during RF deliveries in 20 patients (3 with APs, 17 with VAs). In 11 of 20 patients, RF deliveries were terminated when JR appeared and restarted during atrial pacing at a faster rate than the JR. No transient complete AV block was observed in the 11 patients, however it occurred in 1 of the remaining 9 without atrial pacing (p = 0.25). Small His bundle potentials were recorded at the effective ablation site before the RF delivery in 11 (55%) patients. No patients had any AV conduction disturbances at the end of and after the procedure. APs were successfully eliminated in 2 of 3 patients. VAs were completely and partially eliminated in 10 and 4 of 17 patients, respectively. Conclusions Atrial pacing during RF applications might be helpful to avoid AV conduction disturbances during catheter ablation of APs close to the His bundle and idiopathic VAs originating in the vicinity of the His bundle.